Protecting the Next Seven Generations: Self-Indigenization and the Indian Child Welfare Act - Taylor Elyse Mills (Genealogy)
In 1978, the United States enacted the Indian Child Welfare Act (ICWA) “to protect the best interest of Indian Children and to promote the stability and security of Indian tribes and families by the establishment of minimum Federal standards for the removal of Indian children and placement of such children in homes which will reflect the unique values of Indian culture.” The ICWA was codified to address centuries of genocidal government policies, boarding schools, and coercive adoptions that ruptured many Native families. Now one of the strongest pieces of legislation to protect Native communities, the ICWA was designed to ensure that Native foster children are placed with Native families. Implementing the ICWA has not been smooth, however, as many non-Native foster parents and state governments have challenged the ICWA. While the ICWA has survived these legal challenges, including the recent 2023 Haaland v. Brackeen Supreme Court case, the rise of non-Natives claiming Native heritage, also known as self-indigenizers or “pretendians,” represents a new threat to the ICWA. This Article presents a legal history and analysis of the ICWA to unpack the policy implications of pretendians in the U.S. legal context. This Article demonstrates how the rise of pretendians threatens to undermine the very purpose of the ICWA and thereby threaten the sovereignty of Native peoples. By legally sanctioning the adoption of Native children into non-Native pretendian homes, the ICWA can facilitate a new era of settlers raising Native children, rather than preventing this phenomenon as intended. In response, this Article offers concrete policy recommendations to bolster the ICWA against this threat.